Karst Rock Features Karren sculpturing - Dreybrodt, Wolfgang; Ginés, Angel; Knez, Martin; Slabe, Tadej (Carsologica, 2009)
Rock features are important traces of the formation and development of karst surface. On various karren their record is especially rich, revealing to us the many factors that in diverse conditions formed the karst surface on various carbonate and other rock.We have tried to present the most characteristic rock features and through them the most important factors and processes in the formation of the karst surface, the methods of studying them, and the most outstanding examples.Forty-nine contributing authors offer a wide spectrum of content and examples of rock forms from many karst regions around the world.The first part of the book offers an orderly-organized survey and description of the most characteristic rock forms and presents the physical and chemical corrosion of rock, biocorrosion, the modeling of rock forms, their detailed morphometrics, and numerous descriptions of individual rock forms. The second part is devoted to various examples of rock forms found around the world from Slovenia through North and South America to Australia and Asia.